A SENSITIVE APPROACH TO DETERMINE THE HEALTH STATUS OF I-BEAMS BY MEASURING ITS NONLINEARITY THROUGH THE USE OF RAYLEIGH WAVES - Tse, Peter (2019)
The present study focusses on evaluating the health status of a 1018 steel I-beam using a new nonlinearity parameter defined for Rayleigh waves. This parameter yields a true value of material nonlinearity using the Rayleigh wave harmonics obtained from the experiments carried out at the intact and the impacted state of the I-beam. Accordingly, the evaluated nonlinearity is the inherent and damaged induced nonlinearity. The results show that, for an intact state, the nonlinearity obtained using the new parameter and the experimental results, consist of several peaks and the first peak reaches to the true material nonlinearity. Whereas, in case of damaged state, the nonlinearity parameter at the impacted location shows a sudden increase and reaches a value higher than that of the nonlinearity evaluated at the same location of intact state. Thus, the health status can be easily tracked by comparing the nonlinearity obtained from the current state of the I-beam with that of a physics based nonlinearity parameter obtained at the intact state. In contrast, the velocity and wave attenuation remains unaffected. Thus, by using the new nonlinearity parameter, it has been proven that the inspected I-beam can be easily differentiated whether it is at the intact or impacted state.